2020
DOI: 10.1115/1.4045787
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Phase Inversion Phenomena in Electrical Submersible Pumps Under Oil/Water Flow

Abstract: Despite the common presence of water in oil production, just recently, the scientific community has devoted efforts to studying the influence of emulsion phenomena effects related to oil production using pumps. In the context of this study of phase inversion phenomena, the influence of viscosities and rotational speeds in electrical submersible pumps (ESPs) are evaluated as part of this effort. This study is aimed at investigating the influence of viscosity in phase inversion phenomena. An eight-stage ESP was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…It has been reported that phase inversion depends on the properties of the emulsion (continuous phase oil viscosity and emulsion stability) as well as the shear rate applied to the emulsion (rotational speed and flow rate). Phase inversion occurs at a higher volume fraction of the dispersed phase as the rotational speed increases and the viscosity of the oil continuous phase decreases [15]. The proposed rheological model checks the effect of viscosity on phase inversion but does not reflect the operating conditions or emulsion stability effect.…”
Section: Emulsion Effective Viscosity Variation and Shear Stress Profilesmentioning
confidence: 97%
“…It has been reported that phase inversion depends on the properties of the emulsion (continuous phase oil viscosity and emulsion stability) as well as the shear rate applied to the emulsion (rotational speed and flow rate). Phase inversion occurs at a higher volume fraction of the dispersed phase as the rotational speed increases and the viscosity of the oil continuous phase decreases [15]. The proposed rheological model checks the effect of viscosity on phase inversion but does not reflect the operating conditions or emulsion stability effect.…”
Section: Emulsion Effective Viscosity Variation and Shear Stress Profilesmentioning
confidence: 97%